2012
DOI: 10.1038/nchembio.966
|View full text |Cite
|
Sign up to set email alerts
|

KlenTaq polymerase replicates unnatural base pairs by inducing a Watson-Crick geometry

Abstract: Many candidate unnatural DNA base pairs have been developed, but surprisingly, some of the best replicated adopt intercalated structures in free DNA that are difficult to reconcile with known mechanisms of polymerase recognition. Here we present crystal structures of KlenTaq DNA polymerase at different stages of replicating one of the more promising pairs, dNaM-d5SICS, and show that efficient replication results from the polymerase itself inducing the required natural-like structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
178
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(196 citation statements)
references
References 25 publications
12
178
0
6
Order By: Relevance
“…1A) being a particularly promising example (5-7). Despite lacking complementary hydrogen bonding, we demonstrated that the dNaM-d5SICS UBP is well replicated by a variety of DNA polymerases in vitro (7-10), and that this efficient replication is mediated by a unique mechanism that draws upon interbase hydrophobic and packing interactions (11,12). These efforts then culminated in the first progress toward the creation of an SSO in 2014, when we reported that Escherichia coli grown in the presence of the corresponding unnatural nucleoside triphosphates (dNaMTP and d5SICSTP), and provided with a plasmid-encoded nucleoside triphosphate transporter (NTT2) from Phaeodactylum tricornutum (which we denote as PtNTT2) (13), is able to import the unnatural triphosphates and replicate a single dNaM-d5SICS UBP on a second plasmid (14).…”
mentioning
confidence: 99%
“…1A) being a particularly promising example (5-7). Despite lacking complementary hydrogen bonding, we demonstrated that the dNaM-d5SICS UBP is well replicated by a variety of DNA polymerases in vitro (7-10), and that this efficient replication is mediated by a unique mechanism that draws upon interbase hydrophobic and packing interactions (11,12). These efforts then culminated in the first progress toward the creation of an SSO in 2014, when we reported that Escherichia coli grown in the presence of the corresponding unnatural nucleoside triphosphates (dNaMTP and d5SICSTP), and provided with a plasmid-encoded nucleoside triphosphate transporter (NTT2) from Phaeodactylum tricornutum (which we denote as PtNTT2) (13), is able to import the unnatural triphosphates and replicate a single dNaM-d5SICS UBP on a second plasmid (14).…”
mentioning
confidence: 99%
“…Similarly, in a NMR study on 12-mer 5'-CCTTTCD5SICSTTCTC-3' reveals solution-conformation of the possibility [9]. The structural conformational details of the study have reached on following conclusions [8,10] (i) The mechanism of the insertion of DNAMTP opposite d5SICS was less efficient than the insertion of D5SICSTP opposite DNAM in starting replication. (ii) The nucleobases paired in an intercalated manner, similar to their pairing in free duplex DNA and the mode of pairing depends on the length of the single-stranded template, and (iii) more importantly, the mode of intercalation appeared to depend mostly on sequencespecific interactions of the flanking nucleotides, with the specific packing interactions between the intercalating nucleobases of secondary importance.…”
Section: Fig 1: Dsics-mmo2 and D5sics-dnam Base-pairmentioning
confidence: 99%
“…Romesberg et al [7,8] has successfully engineered replications of some sequences of nucleic acid using hydrophobic base pairs, and they found 60 base-pairs out of about 3,600 combinations which prove the earlier principle to some extent. The base-pair DMMO2-DSICS was found more appropriate for pairing as it shows two contradictory characteristics, hydrophobic for enzymes into DNAfunction and accepts hydrogen-bond when enzymes are replicating the strand.…”
Section: Fig 1: Dsics-mmo2 and D5sics-dnam Base-pairmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent structural and functional data employing hydrophobic nucleobase surrogates with increased stacking ability reveal that DNA polymerase active sites are not only capable of selecting for a correct structure among the pairing nucleotides but also, at least in some cases, capable of enforcing it. [33] This suggests that DNA polymerases might have evolved to favor a coplanar geometry to prevent natural nucleotide mispairing via cross-strand intercalation and instead allow only the more specific, edge-to-edge hydrogen-bonding interactions of the Watson-Crick type. [33] …”
Section: Minor Groove Scanningmentioning
confidence: 99%